THE INFLUENCE OF GADGET MEDIA ON EARLY CHILDHOOD DEVELOPMENT: LITERATURE REVIEW - Vhania Lake; Arina Chusnatayaini (Journal for Quality in Women's Health, 2023)
Background  : The use of gadgets has a detrimental effect on children's interpersonal skills if they are used too often. Method  : The process carried out in this literature review is to review and look for several research journal articles published through an electronic database. Result   : The results of the literature review and discussion of journals can show that there is an influence on the use of gadget media with early childhood development, it is said that Gadgets can affect aspects of cognitive, social-emotional development, religious and moral values, language and physical-motor aspects of children. Conclusion : Now children's social lives are more affected by technology. More often early childhood interacts with gadgets and also cyberspace affects the child's thinking power towards something outside of this, he will also feel unfamiliar with the surrounding environment due to lack of social interaction.